Reseña de: Cobb, Christy, Slavery, Gender, Truth, and Power in Luke-Acts and Other Ancient Narratives - Da Silva, Filipe Noé (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2022)
Reseña de: Cobb, Christy, Slavery, Gender, Truth, and Power in Luke-Acts and Other Ancient Narratives. Cham, Palgrave Macmillan, 2019. 247 pp. [ISBN: 978-3-030-05688-9].